A media independent information service integration architecture for media independent handover - Mateus, A. (2010)
A present challenge in wireless networks is to provide mobility, regardless of the access technology in use, with guaranteed continuity of the service and transparency for the users. One approach to these seamless handovers is to prepare network access in advance, such as pre-authentication, before the mobile device actually physically connects to the desired network. This process requires that the mobile device can discover the parameters of the networks in their geographical area prior to connect to the candidate network. To address these issues, in this paper we propose an integration architecture for a Media Independent Information Service, where several networks elements collaborate in the discovery of information network, and mobile devices collect the desired neighboring network information with a query-response mechanism in two steps. A prototype has been implemented with of the shelf hardware, and several tests have been conducted. Results are better than the ones available in the literature, and network selection is performed in a short period of time.